The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1509/jim.14.0094
|View full text |Cite
|
Sign up to set email alerts
|

The Synergetic Effect of Multinational Corporation Management's Social Cognitive Capability on Tacit-Knowledge Management: Product Innovation Ability Insights from Asia

Abstract: Multinational corporations (MNCs) use their overseas subsidiaries to access tacit knowledge about host countries. It is generally assumed that subsidiary tacit knowledge contributes directly to greater product innovativeness; however, little empirical evidence supports this assumption. In this research, the authors propose a negative direct relationship between subsidiary tacit-knowledge level and MNCs' product innovation ability. The authors then examine the role of social cognitive capability as an attenuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 65 publications
2
41
1
3
Order By: Relevance
“…We propose this to be the reason for its significant but a weaker association with the innovation capability of an organization. Additionally, previous studies on knowledge sharing and innovation have identified tacit knowledge as the heart of innovation and competitiveness and often the primary source of innovation capability and performance of an organization (Cavusgil et al, 2003;Hartono & Sheng, 2016;Sheng, Hartmann, & Qimei, 2015;Von Krogh, Ichijo, & Nonaka, 2000), and the findings from the current study supported the findings of previous research endeavors.…”
Section: Discussing the Findingssupporting
confidence: 85%
“…We propose this to be the reason for its significant but a weaker association with the innovation capability of an organization. Additionally, previous studies on knowledge sharing and innovation have identified tacit knowledge as the heart of innovation and competitiveness and often the primary source of innovation capability and performance of an organization (Cavusgil et al, 2003;Hartono & Sheng, 2016;Sheng, Hartmann, & Qimei, 2015;Von Krogh, Ichijo, & Nonaka, 2000), and the findings from the current study supported the findings of previous research endeavors.…”
Section: Discussing the Findingssupporting
confidence: 85%
“…By engaging in repeated interactions in a variety of foreign markets, a firm enriches its organizational routines, programs, and structures and stores experiential knowledge (Eriksson et al 1997;Sheng et al 2015). This knowledge encompasses both understanding of how to engage in export operations (e.g., how to deal with export trade credits, insure shipments, deal with reverse-logistics, etc.)…”
Section: The Role Of Knowledgementioning
confidence: 99%
“…There are several types of knowledge sharing routines, such as joint training activities, mutual idea and intelligence sharing, and joint knowledge building. Knowledge sharing can augment relationship value by reasons of improved decision making; exchanging relevant information can lead channel partners to a full consideration of available alternatives and risks, and a better utilization of existing explicit and tacit knowledge (Sheng, Hartmann, Chen, and Chen 2015;Srivastava, Bartol, and Locke 2006). In addition, information sharing over time enables the development of transactive memory-knowledge of "who knows what" within a system (Argote, McEvily, and Reagans 2003)-which facilitates relationship coordination and learning (Lewis 2004;Selnes and Sallis 2003).…”
Section: Hypotheses Developmentmentioning
confidence: 99%